Structured Decision-Making as a Leadership Competency in Manufacturing Technology Investment - Jelsi Ratu Berlianne; Pri Hermawan (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
Deciding on investment technology in the manufacturing sector is difficult to do properly. Most of the time, decision options are visible enough to leadership; what makes it harder is getting people with different functional backgrounds and different definitions of success to evaluate those options against the same criteria. This study was conducted at PT J, one of the largest footwear manufacturers in Indonesia, specifically during the calendaring process of rubber outsole production. Material waste is one of the business issues that occurred, where a partial automation pilot had been running for over a year without closing the maximum targeted percentage gap. There is no structured decision framework for choosing the best solution, even though three proposed solutions are available. To provide a structured evaluation of the decision process, this study starts with a Kepner-Tregoe Problem Analysis to define the actual problem before considering alternative solutions. Value-Focused Thinking ensures every function criterion of success is collected and can be generated for possible alternative solutions. To select the best solution, the Analytical Hierarchy Process converted that definition of success into a set of weighted criteria and ranked the best alternative by prioritization assessment. A critical task for the QC Manager was to be alert for any defects. Thickness measurement data was essential for the Production Manager before making any improvements. The Automation Engineer Manager defined a project as a success if the system was reliable, rather than compromising dependability. The plant manager was always asking about what might happen from each of the options for the next investment. These four framings were acquired by putting them into the same evaluation frame at the same time. The only thing that made the most sense was the set of criteria weights. The 18.3% combined weight for cost was second to quality at 30.9%. This systematized process did not change these managers' thinking. It, in fact, found the first opportunity to see how they really think